Does democracy cure a resource curse? - Iikka Korhonen (Bank of Finland, Institute for Economies in Transition (BOFIT), 2004)
In this paper we utilise a large and reasonably detailed dataset to show that a greater level of democracy in a country's political institutions can alleviate the widely known resource curse.Raw material abundance affects per capita growth negatively, an effect that seems to work through several different channels. Resource-abundant countries have a lower degree of democracy and political rights, and also a lower level of educational attainment. These factors inhibit growth.On the other hand, countries with large extractive industries exhibit high levels of investment.The effects of resource abundance differ for different raw material types, and the largest negative effect on growth appears to come from non-fuel extractive raw materials.
URN:NBN:fi:bof-201408071986
Keywords: 330; Economic growth; resource curse; cross-country regression; development; governance; institutions